2008
DOI: 10.2106/jbjs.f.01029
|View full text |Cite
|
Sign up to set email alerts
|

Hemiarthroplasty for the Rotator Cuff-Deficient Shoulder

Abstract: Hemiarthroplasty can provide good long-term results in rotator cuff-deficient patients with glenohumeral arthritis. Patients who have preoperative forward elevation of >or=90 degrees benefit the most. A low complication rate can be expected for this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…Little has been published on concurrent rotator cuff repair; Goldberg 22 and Pollock et al 7 suggested that it improves outcome; however, they found no statistical difference in their series of cuff-deficient arthritis treated with stemmed hemiarthroplasty.…”
Section: Discussionmentioning
confidence: 98%
“…Little has been published on concurrent rotator cuff repair; Goldberg 22 and Pollock et al 7 suggested that it improves outcome; however, they found no statistical difference in their series of cuff-deficient arthritis treated with stemmed hemiarthroplasty.…”
Section: Discussionmentioning
confidence: 98%
“…Williams et al, reported 86% of very good results; (11) Field et al, 63%; (9) Zuckerman et al, demonstrated 87% of satisfaction among patients; (12) Sanchez-Sotelo et al found 67% of very good results; (13) and Goldberg et al, 76%. (14) …”
Section: Discussionmentioning
confidence: 99%
“…Over a mean follow-up of 3.7 years, Goldberg et al 18 obtained a satisfaction rate of 78%, with mean improvements of 33° in elevation and 23° in external rotation through using conventional hemiarthroplasty. The patients with a minimum elevation of 90° achieved the best results.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional total arthroplasty of the shoulder is now contraindicated in patients presenting arthropathy of the rotator cuff because of the high rate of loosening of the glenoid component. The current alternative arthroplasty options for arthroplasty of the rotator cuff are non-conventional (CTA ® ) partial arthroplasty and use of a reverse prosthesis 3, 16, 17, 18…”
Section: Introductionmentioning
confidence: 99%